Behavioural repertoire of termites in corpse management: A comparison between one-piece and multiple-pieces nesting termite species - da Silva, Luiza Helena Bueno [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Elsevier, 2018)
Corpse disposal is an essential adaptation to social life. This behaviour promotes nest hygiene and prevents the spread of pathogens in the colony of social insects. The current study verified the corpse management in two termite families towards cadavers of different origins. We carried out bioassays with subcolonies of Cryptotermes brevis and colonies of Cornitermes cumulans, in which corpses of termite workers from the same colony, from another colony and from another species were introduced. The results showed that C. brevis consumed the corpses regardless of their origin, but they avoided the chitinous parts of the head. In this species, consumption of dead individuals, besides performing a hygienic function, seems to be a strategy for nitrogen and water acquisition. In the C. cumulans species, interspecific and intercolonial corpses were covered with soil and faeces after being groomed. Nestmate corpses were entombed, transported to the nest or ignored after being submitted to grooming. Our findings indicate that a one-piece nesting termite, as C. brevis, exhibited a simplified corpse management repertoire in relation to that performed by C. cumulans, a multiple-piece nesting species, whose approach was more complex and diverse. Behavioural responses are associated with the nesting of the species.
Keywords: Cannibalism; Cornitermes cumulans; Corpse-burying behaviour; Cryptotermes brevis; Isoptera; Undertaking behaviour